The hidden racism of linguistics - Frawley, David (2007)
Western linguistics particularly its study of Eurasian languages, arose against a background of Eurocentrism, colonial racism, nationalism and related theories, later espoused by Nazism and other White Supremacy movements. The following article argues that significant traces of this racism remain in contemporary Indology and South Asian lingustics - casting a long shadow over how the world is viewed. This is particularly true of the study of India in the Western world. - Reproduced.
Keywords: Linguistics